Penerapan Terapi Psikoreligius Dalam Mengatasi Trauma Kekerasan (Studi Kasus Pada Klien "W" di LPKA Palembang) - taufiqurrahmana, Awal; Razzaq, Abdur; rasmanah, Manah (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This research is entitled "Application of Psychoreligious Therapy in Overcoming Violent Trauma (a case study on client "w" in LPKA Palembang" This research uses a qualitative approach with a case study research method. The research subject is the client "W". The results of this study indicate that before carrying out the therapy process it is still at a high level where there are several aspects that make clients experience excessive trauma, cannot control their own thoughts, have feelings of being easily restrained, do not want to have relationships with the opposite sex, are depressed when it comes to marriage.